Duties to endangered species (BioScience) - Rolston, Holmes, 1932-2025, author; American Institute of Biological Sciences, publisher (Colorado State University. Libraries, 1985)
Neither scientists nor ethicists have realized how concern for endangered species requires an unprecedented mix of biology and ethics. The usual approach says that there are only duties to other persons concerning species. Species are resources, rivets in ecosystems, a Rosetta stone for natural history. Direct duties to species requires analysis of what a species is, a dynamic life form, which the individual inherits, instantiates, and passes on. The wrong that humans are doing is stopping the historical flow in which the vitality of life is laid.
Keywords: ecosystems; biological science; conservation; Endangered Species Act; ethics; altruism